Corn response to selected soil health indicators in a Texas drought - Kabindra Adhikari (Elsevier, 2021)
The phrase “soil health” describes the condition of a soil in terms of its physical, chemical, and biological properties. The relationship between soil health and crop yield is rather complex, and quantifying their spatial characteristics at field scale is often limited in the literature. To explore the significance and spatial characteristics of soil health and its indicators in crop production, field-based research was conducted in 2018 at the Blackland Research Center, Texas with the following objectives: (i) to quantify soil health indicators of the Haney Soil Health Tool across a corn field; (ii) to relate soil health status to drought-year corn yield using geospatial techniques; and (iii) to evaluate the relationship among soil health, corn yield, and soils types. We collected 218 samples from 0 to 10 cm soil depth in a 27-ha field following a 35 m × 35 m grid sampling scheme. Samples were analyzed for water extractable organic carbon (WEOC), total nitrogen, nitrate-nitrogen, ammoniacal-nitrogen, and 24-hr CO2 evolution (1-day CO2). Analyses results were used to calculate a soil health value based on Haney Soil Health Tool. The field had an average soil health value of 8.5 (±2.2), and corn yield of 2.9 t ha−1 (±1.3); however, corn yield was more variable (CV > 43%) than soil health (CV = 26.7%). Overall, soil samples with lower values of 1-day CO2, WEOC, and organic nitrogen indicated a lower soil health value, which generally corresponding to lower corn yield. Corn yield may be weakly predicted by soil health (Corn yield = −0.29 + 0.39 × Soil health value, R2 = 0.28). Soil type and rainfall exhibited measurable effects upon the calculated soil health value; corn yields were greater for Houston Black clay than Austin silt clay under drought-year conditions. The variation in drought-year corn yield can be explained by the soil health and its indicators in Texas Blackland soils. Further research is necessary to verify the relationship in differing soil types, management scenarios, and annual rainfall totals.